Preliminary trial of woody debris addition on the return of invertebrates to restored bauxite mines in the jarrah forest of Western Australia - Lythe, M.; Majer, Jonathan; Stokes, V. (Wiley-Blackwell Publishing Ltd, 2017)
Woody debris is an important component of forest ecosystems, but its use in mine site restoration has been limited and it can be slow to build up naturally. A new technique of spreading snipped wood waste onto restored mine pits prior to seeding has been subjected to a preliminary trial at Alcoa's Huntly mine site, in the northern jarrah forest of south-western Western Australia. We examined whether the application of snipped wood during restoration encourages the return of ground- and litter-dwelling invertebrates without negatively suppressing plant establishment. Invertebrates were sampled across three seasons from experimental plots treated with 0 t/ha (control), 100 t/ha or 300 t/ha snipped wood waste. Invertebrate communities in treatment plots comprised higher numbers and diversity of wood and litter decomposers such as mites, Diplopoda, Dermaptera and Blattodea than control plots. Plant responses were variable, with wood treatment resulting in lower tree and overall plant density but having no effects on plant species richness or plant cover. Wood treatment plots were associated with higher soil nitrogen than controls. We hypothesise that the use of a fine wood treatment at the lowest rate of 100 t/ha (approximately 30% wood cover) is likely to enhance the diversity and abundance of invertebrates in restored areas, with minimal effect on plant establishment. Encouraging a diverse invertebrate fauna to recolonise restoration should help speed up succession and ecosystem functions such as decomposition and nutrient cycling, and more quickly return the land to previous ecosystem values.